Noble metal ions incorporated in lattice points of perovskites - water gas shift activity of BaCe1-xPtxO3-d - Jijil, Chamundi P.; Rajarajan, A. K.; Devi, R. Nandini (56th DAE-Solid State Physics Symposium (SSPS), 2012)
Recently precious metals supported on oxides were reported to be very promising catalysts for the lower-temperature WGS reaction. Here we report the synthesis of platinum doped barium cerate and its use as catalysts for WGS reaction. It has been found that maximum CO conversion was obtained at 350 degrees C which enhanced after the first cycle. XPS analysis shows that after the first cycle more ionic Platinum species are present on the surface of the catalyst. Neutron diffraction at room temperature shows that the oxygen vacancies are in the O2 position and increases with increasing Pt substitution.
56th DAE-Solid State Physics Symposium (SSPS), SRM Univ, Kattankulathur, INDIA, DEC 19-23, 2011
Keywords: BaCeO3; Neutron diffraction; Platinum catalysis; WGS reaction

Pt States in BaCe0.98Pt0.02O3-delta during start up and shut down operations under different conditions: stability and activity of ionic Pt in water gas shift reaction - Rajesh, Thattarathody; Devi, R. Nandini (Catalysis Letters, 2014)
Stability of Pt species in doped BaCeO3 perovskites under Water gas shift reaction conditions is studied using X-ray absorption spectroscopy and in situ powder X-ray diffraction. The catalyst BaCe0.98Pt0.02O3-delta has Pt in +2 oxidation state and is found to be stable in the ionic form under reaction conditions as well as under various highly reducing shut down and start up conditions. In-situ XRD under Water Gas shift reaction conditions also reveals the Pt ions to be highly stabilized in lattice and no egress is observed.
Keywords: BaCeO3; Deactivation; platinum; WGS reaction; XPS